(untitled) (Research, Society and Development, 2022)
Purpose: to analyze the probability of survival and prognostic factors after five years of prostate cancer diagnosis in Florianópolis, Santa Catarina. Methods: It is a cohort study with data from the Population-Based Cancer Registry (2008 to 2012) and the Mortality Information System (2008 to 2017) about prostate cancer diagnoses. The survival time was the interval between the date of diagnosis and the date of death or the end of follow-up (60 months). The covariates were age, ethnicity, education, marital status, and extension of disease. Survival analyses, Kaplan Meier analysis, and risk factor analyses, Cox model, were stratified by age group (≤59 years, 60 to 69 years, ≥70 years). Results: 836 men diagnosed with prostate cancer were included and 103 died of cancer during follow-up. The probability of survival was 87,7%. Increasing age reduced survival after the cancer diagnosis, while the metastatic extent of disease was the only independent factor associated with death. Conclusion: Age and advanced stage at the time of cancer diagnosis are key determinants of disease prognosis. It is emphasized the importance of minimizing the time between the onset of symptoms, diagnosis, and start of treatment of prostate cancer.